2011
DOI: 10.1016/j.joms.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Imaging for Lower Third Molars: Is There an Implication for Surgical Removal?

Abstract: IntroductionSurgical removal of impacted third molars is maybe the most frequent procedure in oral surgery. Damage to the inferior alveolar nerve (IAN) is a typical complication of the procedure with incidence rates reported at between 1 and 22%. The aim of this study was to identify factors that lead to a higher risk of IAN impairment after surgery. MethodA total of 515 surgical wisdom tooth removals having 3D imaging prior to surgical removal were retrospectively evaluated for IAN impairment, along with 3D i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 21 publications
5
52
0
2
Order By: Relevance
“…CBCT imaging is a relatively new modality that has the advantage of displaying the bucco-oral aspect of the relation between the molar and the canal, and several studies have assessed the use of CBCT before surgical removal of mandibular third molars and found CBCT to be superior to panoramic images to display the relation between the molar and the mandibular canal. [15][16][17][18][19]25,34 However, no previous study has examined whether the treatment plan will change when CBCT is available compared with merely a panoramic image and scanograms, or which factors that have an impact on deciding on coronectomy vs surgical removal of the entire tooth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT imaging is a relatively new modality that has the advantage of displaying the bucco-oral aspect of the relation between the molar and the canal, and several studies have assessed the use of CBCT before surgical removal of mandibular third molars and found CBCT to be superior to panoramic images to display the relation between the molar and the mandibular canal. [15][16][17][18][19]25,34 However, no previous study has examined whether the treatment plan will change when CBCT is available compared with merely a panoramic image and scanograms, or which factors that have an impact on deciding on coronectomy vs surgical removal of the entire tooth.…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study used absence of bony separation between the roots and the canal on CBCT as an eligible reason for deciding on coronectomy instead of surgical removal. It was suggested that coronectomy should be the treatment of choice when there was a high risk for IAN injury.…”
Section: Role Of Cbct On Treatment Plan Of Lower M3mentioning
confidence: 99%
“…1 Third molar surgery is the most common cause of injury to the inferior alveolar nerve, 2 so the knowledge of the exact location of the nerve can reduce surgical complications. 3 If you decide to make a third molar surgery the radiographic examination of the teeth and surrounding structures is required.…”
Section: Discussionmentioning
confidence: 99%
“…1 The open extraction of third molars is one of the most commonly used procedures in dentoalveolar surgery, and after the surgery several complications can occur, 2 therefore, location of the IAN in the surgical field is important because it can improve the reduction of complications, surgical planning, and quality of care. 3 A preoperative evaluation of the exact location of the IAN and the roots of the mandibular third molar would help avoiding sensory deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…We do not agree that any conventional technique, such as tube shift, can provide the amount of information about risk factors necessary for informed consent and safe surgical procedures. 6 Of course, the additional radiation dose has to be justified by an individual indication and risk assessment.…”
Section: No Plane Is the Best One -The Volume Is!mentioning
confidence: 99%